Spectroscopic and electronic properties of a copolymer and its metal complexes: A theoretical and experimental study - Acikses, Aslisah; Hekim, Seda; Oksuz, Fethiye (Elsevier, 2019)
A copolymer containing 4-Diethanolaminomethyl Styrene (DEAMSt) monomer with Benzyl Methacrylate (BMA) monomer units were synthesized by free radical solution polymerization technique using AIBN as a free radical initiator and 1,4-dioxane as a solvent at 60 degrees C. The metal complexes were prepared by reaction of the copolymer used as ligand poly(DEAMSt0.70-co BMA) and Ni(II), Co(II) and Zn(II) metal ions in presence of ethanol and dilute NaOH at 65 degrees C for 48 h in pH 6. The structure of copolymer used as ligand and polymer-metal complexes were characterized by (FT-IR), H-1 NMR, elemental analysis, and SEM-EDX techniques. For the theoretical calculations (FT-IR and H-1 NMR spectrum) the Hartree-Fock (HF) theory with 6-31G (6D, 7F) basic set was used. In addition, the highest occupied molecular orbital (HOMO), the lowest unoccupied molecular orbital (LUMO) energies were investigated. A good agreement has been found between the theoretical and experimental FT-IR and H-1 NMR results.
Keywords: 4-Diethanolaminomethyl Styrene; Benzyl Methacrylate; Hartree-Fock theory; FT-IR; H-1 NMR spectra; HOMO and LUMO energies